Frequency of HLA-A＊03 associates with HIV-1 infection in a Chinese cohort - Zhang, Weilun; Wang, Li; Hong, Kunxue; Liu, Yanxin; Su, Bing; Xu, Cheng; Xu, Jianqin; Ruan, Yuhua; Shao, Yimin; Zheng, Dexian (Science China. Life sciences, 2013)
During the early mid-1990s, a number of rural farmers across central China were employed to the unregulated plasma- selling-activity and many of them were infected by HIV-1. However, AIDS progression in the former blood donors （FBDs） is various. The aim of this study is to assess human leukocyte antigen （HLA） class I allele distribution in FBDs and evaluate its association with HIV-1 infection and disease progression. A total of 353 FBDs were enrolled in the cohort including 294 ART na＇fve HIV-1 seropositive and 59 HIV-1 seronegative age-matched subjects. The viral load and CD4/CD8 T cell counts were assessed in all subjects. Compared with HIV-seropositive group, the frequency of HLA-A＊03 in control was significantly higher. After classifying the HLA-B alleles of the subjects according to the presence of Bw4/Bw6 serological epitopes, detri- mental effect of HLA Bw6/Bw6 homozygosity was also confirmed in the HIV-seropositive subjects. This study provides nov- el evidence on HLA class I allele distribution and association of HLA-A＊03 frequency with HIV-1 infection and viremia in the HIV-1 infected FBDs, which may throw light on intervention strategy for the HIV-1 infection and our understanding how host immunity and genetic background affect HIV infection and AIDS progression.